Larvicidal, Histopathological, Antibacterial Activity of Indigenous Fungus Penicillium sp. Against Aedes aegypti L and Culex quinquefasciatus (Say) (Diptera: Culicidae) and Its Acetylcholinesterase Inhibition and Toxicity Assessment of Zebrafish (Danio rerio) - Ragavendran, Chinnasamy; Manigandan, Venkatesan; Kamaraj, Chinnaperumal; Balasubramani, Govindasamy; Prakash, Joy Sebastian; Perumal, Pachiappan; Natarajan, Devarajan (Frontiers in Microbiology, 2019)
Fungal metabolites are considered to be most efficient tools to overcome the issues related to insecticide resistance and environmental pollution. The present study focus on evaluate the mosquito larvicidal efficacy of metabolites of seven indigenous fungal isolates (Penicillium spp, Aspergillus niger, A. flavus, A. parasiticus, Rhizopus spp, Mucor spp and Aspergillus spp) on the larvae of Aedes aegypti and Culex quinquefasciatus under the laboratory condition. The preliminary screening of the isolate, Penicillium spp, showed better larvicidal effect when compared to other fungi. The fungus was grown on Potato Dextrose Broth (PDB) in the laboratory (at 25°C) and maintained in the relative humidity (at 76±4% for 15 days). Larvicidal potency of mycelial ethyl acetate extract (MEAE) of Penicillium spp was performed against 1st to 4th instars larvae of Ae. aegypti and Cx. quinquefasciatus using four different concentrations (100, 200, 300 and 500µg/ml) that showed resulted better larval mortality values (µg/ml) of LC50=6.554, 5.487, 6.874, 6.892, and the LC90= 11.486, 10.366, 12.879, 13.865 for Ae. aegypti and (LC50= 7.000, 13.943, 18.129, 25.212 µg/ml and the LC90=12.541, 23.761, 30.923, 41.696 for Cx. quinquefasciatus). Exposure of metabolite to larvae resulted in behavior changes i.e excitation, up and down with aggressive movement, anal papillae biting behavior. Further, the larvae treated with Penicillium spp metabolite exhibited significant reduction in the levels of acetylcholinesterase. The IVth instar mosquito larvae treated with the 500 µg/ml mycelia extract showed severe histological damages. During the antibacterial analysis of Penicillium sp.,- mycelium the maximum growth inhibition zone was recorded in S. dysenteriae (31.2 mm) and K. pneumoniae (31.1 mm) followed by others. In addition, to check the toxicity of Penicillium spp MEAE against embryos of Zebrafish, a model system, using different concentrations of metabolites (1.0, 0.5, 0.125mg/ml, 30, 3.0, and 0.5 μg/ml) and life-stage parameters were observed at 124 hpf. Furthermore, the FTIR and GCMS spectrum analysis of mycelium reflected several chemical compounds. The outcome of the study clearly shows that Penicillium spp metabolites served could serve as an ideal eco-friendly, single-step and inexpensive source for the control of Ae. aegypti and Cx. quinquefasciatus larvae.